PENERAPAN METODE SIMPLEKS UNTUK OPTIMALISASI PENGGUNAAN ALAT BERAT PADA PEKERJAAN GALIAN DAN PENGANGKUTAN - Majid, Haqya; Lila Ayu Ratna Winanda; Munasih (Jurnal Teknik Sipil, 2025)
Most construction projects currently use heavy equipment during their implementation. The purpose of using heavy equipment is to make it easier to do work so that work can be done more easily and quickly. The Babon River is a river that crosses the city of Semarang with a watershed area of ​​119,417 km2 and a length of around 17 km starting from downstream of Pucang Gading Dam to the estuary passing Karang Roto Dam. The condition of the Babon River, which is experiencing channel narrowing and shallowing, has reduced the capacity of the river's cross-section to carry flood discharge, so that during the rainy season, floods often occur which inundate the area around the Babon River. Therefore, it is necessary to normalize the Babon River so that its function continues to run well so that it can overcome flooding in the area around the Babon River. Through the preparation of this journal the author tries to analyze the productivity of each heavy equipment used, namely: PC-200 Excavator, Hitachi ZX210LC-5g Long Arm Excavator + pontoon, Hino FG 260 JJ Dump Truck, Hino 136 HD Dump Truck, and Dump Truck Hino FM 260 JD. Based on the analysis results, the productivity results of the PC-200 Excavator were: 228.3 m3/hour, the productivity of the Hitachi ZX210LC-5g Long Arm Excavator + pontoon: 73.6 m3, the productivity of the Hino FG 260 JJ Dump Truck: 17.54 m3/hour, Hino 136 HD Dump Truck productivity: 11.76 m3/hour, Hino FM 260 JD Dump Truck productivity: 25.23 m3/hour. Keywords: Heavy Equipment, Heavy Equipment Optimization, Heavy Equipment Productivity